2016
DOI: 10.15381/anales.v77i2.11812
|View full text |Cite
|
Sign up to set email alerts
|

Capacidad antioxidante del fruto de la Opuntia apurimacensis (ayrampo) y de la Opuntia ficus-indica (tuna)

Abstract: ResumenIntroducción. En la tuna existen compuestos antioxidantes, pero, se desconoce si hay en el ayrampo. Objetivo. Determinar la capacidad antioxidante de Opuntia apurimacensis (ayrampo) y de Opuntia ficus-indica (tuna). Diseño. Estudio analítico observacional. Lugar. Laboratorio de Bioquímica Clínica y Nutricional, Centro de Investigación de Bioquímica y Nutrición, Facultad de Medicina, Universidad Nacional Mayor de San Marcos, Lima, Perú. Material biológico. Fruta fresca (ff) de Opuntia apurimacensis (ayra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…The peel of purple prickly pear (18.50 mg/mL) presented greater antioxidant activity against the radical DPPH compared with the remaining tissues of the yellow prickly pear (16.73-27.99 mg/mL). In contrast, Jorge and Troncoso [62] found that the antioxidant capacity was provided by vitamin C, its contribution is greater than 50% of the total antioxidant capacity of the prickly pear. Prickly pears have pulps and peels of different colors.…”
Section: Phytochemical Profile and Antioxidant Capacity Of Commercial...mentioning
confidence: 84%
See 1 more Smart Citation
“…The peel of purple prickly pear (18.50 mg/mL) presented greater antioxidant activity against the radical DPPH compared with the remaining tissues of the yellow prickly pear (16.73-27.99 mg/mL). In contrast, Jorge and Troncoso [62] found that the antioxidant capacity was provided by vitamin C, its contribution is greater than 50% of the total antioxidant capacity of the prickly pear. Prickly pears have pulps and peels of different colors.…”
Section: Phytochemical Profile and Antioxidant Capacity Of Commercial...mentioning
confidence: 84%
“…In a study conducted by Jorge and Troncoso [62] on red prickly pears collected in Huancavelica (Peru), the vitamin C content was 36.1 mg/100 g. Similarly, Monroy-Gutiérrez et al [63] the vitamin C content in the cultivars "Rojo Pelón" and "Liso Forrajero" (both red prickly pears) ranged from 42.54 to 16.00 mg/100 mg, where the highest value was presented 21 days after evaluation in the "Rojo Pelón" variety (Table 11).…”
Section: Major Parts Of Tuna or Prickly Pears With Red Peel Fruits (A...mentioning
confidence: 99%
“…La actividad antioxidante encontrada en ambas variedades de tuna, es por su contenido de fenoles y flavonoides, lo cual está en relación con el trabajo realizado en el fruto de Opuntia ficus indica, donde se reporta la actividad antioxidante por su contenido de vitamina C y polifenoles 24 .…”
Section: Ensayounclassified
“…Opuntia ficus-indica , commonly known as nopal, is a shrub species of the genus Opuntia of the cactus family, widely consumed in Mexico, which has been documented with anti-inflammatory, hypoglycemic, stomach ulceration inhibitory, neuroprotective, and antioxidant properties. It has also been used to treat diabetes, burns, bronchial problems, asthma, and indigestion [ 31 , 32 ]. Tradescantia pallida is a species of herbaceous and perennial plant endemic to Mexico, used mainly ornamentally; however, it has been used in the biomonitoring of contamination through the frequency of micronuclei (somatic mutations induced by carcinogens), in addition to having antioxidant, α-glucosidase inhibitory, antimicrobial, and hepatoprotective activity [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%